Gradient Echo-Additional Track Sign for Easy Detection of Vertebral Artery Dissection. Issue 1 (June 2018) - Ojha, Pawan; Nagendra, Shashank; Patil, Sarika; Singh, Rakesh; Chheda, Akash
Abstract: Vertebral artery dissection (VAD), a well-recognized cause of stroke in young, can be easily missed on magneto resonance angiography of the brain. Computed tomography and catheter−based angiography are often used to detect arterial dissection, but they have their limitations. Here, we discuss cases of stroke in young where the presence of the additional track sign on a gradient echo sequence provided the clue to VAD being the etiology of stroke. This sign observed on the routine magnetic resonance imaging brain might be of great help to clinicians and radiologists for the easy detection of VAD.